Mussolini dans les uchronies italiennes - Emiliano Marra (Les Grandes Figures Historiques dans les Lettres et les Arts, 2022)
From the Second World War to the present day, a flourishing crop of uchronias allowed Italian authors to grapple with the country’s Fascist past. Marra frames these works within their political and historical context, firmly linking those published in the immediate aftermath of the war to far-right activism, while later works, in reaction to the first, were more critical of Fascism, and later still, adopted a more playful angle (thus Massimo Mongai recasts “Benny” Mussolini as a placid Italian-American author of science-fiction and uchronia). Political activism has not disappeared for all that, as the far-right CasaPound movement recently demonstrated by sponsoring Mussolini-centred uchronias. Marra concludes that such partisan works are narratively flawed, for in order to vindicate Mussolini and Fascism, they are forced to distort History in a more artificial way than other, more distanced uchronias.